2018
DOI: 10.1002/joa3.12080
|View full text |Cite
|
Sign up to set email alerts
|

Acute pulmonary hemorrhage during atrial fibrillation HotBalloon ablation

Abstract: A 64‐year‐old man with an atrial septal defect was referred for HotBalloon ablation of symptomatic drug‐resistant paroxysmal atrial fibrillation. Pulmonary vein (PV) isolation was achieved using a SATAKE HotBalloon ablation system, which was inserted into the left atrium through the deflectable guiding sheath via the atrial septal defect. During ablation of the right superior pulmonary vein carina, the HotBalloon dropped to the left atrium. Hemoptysis and respiratory failure was then observed, and the patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Despite continuous efforts to refine ablation strategies and titrate energy delivery, all these techniques still cause collateral damage to cardiac and extracardiac tissue, like the esophagus and the bronchus. [2][3][4][5][6][7][8][9] For this reason, delivered energy levels must be reduced, leading to decreased efficacy and subsequent durability of the ablation lesions.…”
mentioning
confidence: 99%
“…Despite continuous efforts to refine ablation strategies and titrate energy delivery, all these techniques still cause collateral damage to cardiac and extracardiac tissue, like the esophagus and the bronchus. [2][3][4][5][6][7][8][9] For this reason, delivered energy levels must be reduced, leading to decreased efficacy and subsequent durability of the ablation lesions.…”
mentioning
confidence: 99%
“…During the balloon-based ablation, it has been reported that guidewire-related complications are rarely caused by a guidewire being positioning deep in the distal PV or left atrial appendage, as manifested by a PV hemorrhage or LA perforation. 1 , 2 The incidence is reported to be 0.35% during cryoballoon ablation, but it is unknown during HBA. 3 Electrophysiologists should always be aware of the position of the guidewire tip while advancing the balloon to prevent any PV injury or left atrial appendage perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Yamasaki et al reported a cardiac tamponade case needed pericardiocentesis during the LSPV isolation. In their case, the guidewire inadvertently advanced toward the left appendage and caused roof injury …”
Section: Discussionmentioning
confidence: 99%